Comprehensive design of disturbance observer and non‐singular terminal sliding mode control for reusable launch vehicles. Issue 12 (1st August 2015) - Su, Rui; Zong, Qun; Tian, Bailing; You, Ming
Abstract : A multivariable non‐singular terminal sliding mode control (NTSMC) strategy is developed combining disturbance observer (DO) technique for the six‐degree‐of‐freedom reusable launch vehicles. First of all, the control‐oriented model is established, followed by a design of finite‐time DO, which is to estimate the model uncertainties and external disturbances. Second, based on the disturbance estimation, a composite controller combining multivariable NTSMC is developed to make the attitude tracking errors converge to zero in finite time. And then the stability of the closed‐loop system is guaranteed through Lyapunov theory. Finally, the simulation results illustrate that the comprehensive control strategy performs well in tracking the guidance commands in spite of model uncertainties and external disturbances.